Performance Optimization of Microbes from Shrimp Pond Sediment by Adding EM4 In Nitrification Process for the Treatment of Wastewater Containing High Ammonia Concentration - HANIES AMBARSARI; MUHAMMAD RAHMADI HARAHAP (Indonesian Society for microbiology, 2017)
Â In liquid wastes, especially domestic wastewater, many organic substances are mixed causing water quality degradation, one of them is ammonia. Liquid wastes containing ammonia can be treated using an activated sludge system. One of the active sludge that can be used is shrimp pond sediments. This experiment investigated the performance of microbes in shrimp pond sediments with the addition of EM4 in nitrification process for the treatment of wastewater with high ammonia concentration in a 8 L batch reactor capacity. The results show that the addition of shrimp pond sediment as the active sludge can remove high ammonia level almost completely and there is known interaction between time and variation of shrimp pond quantity (p value <0,05) to the decreasing of ammonia level. Efficiency of decreasing the concentration of ammonia up to 100% can be reached on the 15th day in each treatment. The addition of EM4 can shorten the decreasing of ammonia level by 50%.Â Keywords: Nitrification, Ammonia, Shrimp Pond Sediment, EM4, Activated Sludge